STUDENT PERCEPTIONS OF THE CHILD-FRIENDLY SCHOOL CONCEPT AND SCHOOL LITERACY MOVEMENT AFFECT STUDENTS' LEARNING MOTIVATION - Khomsin, Achmad; Jaya, Indra; Utami, Nidya Chandra Muji (UIN Sumatera Utara Medan, 2024)
This study aims to determine the influence of students' perceptions of the concept of child-friendly schools and the school literacy movement on the learning motivation of high-grade students in elementary schools. The research method used is a survey with data collection using questionnaires, while data analysis uses descriptive statistics and inferential statistics with multiple linear regression analysis as a hypothesis test. Grade V students in four public elementary schools in Cimanggis sub-district, Depok City were selected as research samples through the use of simple cluster random sampling techniques. The results showed that all regression models tested partially had calculated values of thitung > ttabel and significance values (Sig.) < (α = 0.05) which means that there is a significant influence on students' perceptions of child-friendly schools on student learning motivation and students' perceptions of school literacy movements on student learning motivation, and the regression models tested simultaneously have Fhitung > Ftabel values and significance values (Sig.) < (α = 0.05) which This means that there is a significant influence on students' perceptions of child-friendly schools and the school literacy movement simultaneously on student learning motivation. Based on these results, the conclusions of this study are: first, students' perceptions of child-friendly schools have a significant effect on the learning motivation of grade V elementary school students; second, students' perceptions of the school literacy movement have a significant effect on the learning motivation of grade V elementary school students; third, students' perceptions of child-friendly schools and the school literacy movement simultaneously have a significant effect on the learning motivation of Grade V elementary school students.